2018
DOI: 10.21608/ejbo.2018.2943.1153
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Lead Stress in Triticum aestivum by Seed Priming in Aqueous Extracts of The Macroalgea Halimeda opuntia and Codium fragile

Abstract: T HE MAJOR aim was to assess the effects of lead stress on Triticum aestivum (cv. Gemmeza R2) and to evaluate the role of seed priming in the aqueous extract of Halimeda opuntia or Codium fragile in the alleviation of these harmful effects. Seven days old T. aestivum seedlings growing from primed seeds were subjected to the sub-lethal concentration (400ppm) of lead nitrate (Pb (NO 3) 2), then left to grow for 14 days. Results revealed that the lead nitrate significantly decreased root length, shoot height and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Even though literature on this specific research topic is limited, the positive effect of SWE, and especially of Codium spp. extract, in promoting wheat germination (also in controlled salinity conditions) are reported in other studies [ 51 , 52 ]. Codium spp., as other macroalgae, appear to be rich in phytohormones such as cytokinin, gibberellins, and auxins [ 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Even though literature on this specific research topic is limited, the positive effect of SWE, and especially of Codium spp. extract, in promoting wheat germination (also in controlled salinity conditions) are reported in other studies [ 51 , 52 ]. Codium spp., as other macroalgae, appear to be rich in phytohormones such as cytokinin, gibberellins, and auxins [ 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 68%
“…Some studies showed promising results derived from the application of Codium spp. extract to enhance seed germination and seedlings performance of different crop species [ 46 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of macroalgae extract to act as biostimulants is the result of its composition in bioactive compounds, specifically those that are plant growth hormones; cytokinins, auxins, abscisic acid and gibberellins, among others [102]. While auxins provide the potentiality for plant ageing and plant tissue growth, cytokinins are involved in cell division and nutrient transport and stand out as the most promising plant biostimulator [103]. As for gibberellins, their main advantage is seed germination and fruit development, and in the case of abscisic acid, their effects focus on the response to stress factors [102,104].…”
Section: Macroalgae As Bio-resource For Biostimulants Productionmentioning
confidence: 99%
“…Increasing the carotenoids content by metal stress refers to an increase in the non-enzymatic antioxidant defense, offering its free radical scavenging employment (Shabani et al, 2016). The inhibited Fv/Fm (photochemical efficiency of PS II) reflected a depletion of the photosynthesis process that positively correlated with the blockage of electron transport, reduction of Calvin cycle enzymes, and disruption of chloroplast ultrastructure (Nessim & El-Shenody, 2018).…”
Section: Photosynthetic Parameters Under Heavy Metal Stress and S Ext...mentioning
confidence: 99%
“…Wheat (Triticum asetivum L.) is the most pivotal cereal crop globally. Nearly one-third of the world's population consumes it as a staple diet, ensuring the nutritional security of people worldwide (Nessim & El-Shenody, 2018). The over-utilization of chemical fertilizers could cause metal accumulation and high toxicity in wheat crops (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%